Hippocratic recipes : oral and written transmission of pharmacological knowledge in fifth- and fourth-century Greece - Totelin, Laurence M. V. (Studies in Ancient Medicine, 2009)
Hippocratic Recipes is the first extended study of the pharmacological recipes included in the Hippocratic Corpus. The recipes, found mostly in the gynaecological and nosological treatises, are here examined both from a philological and a sociocultural point of view. Drawing on studies in the fields of classics, social history of medicine, and anthropology, this book offers new insights into the production and use of pharmacological knowledge in the classical world. In particular, it assesses the deep interactions between oral and written traditions in the transmission of this knowledge. Recipes are addressed as texts, but the existence of 'missing links' in the written tradition are acknowledged.